Residence of Peter the First in Kolomenskoye in the Perspective of the Complex Historical – Archeological Investigation - Baranova, Svetlana I.; Beliaev, Leonid A. (Actual Problems of Theory and History of Art, 2022)
Kolomenskoye was a tsars’ residence through the 16th–19th centuries, and in the second half of the 17th century, it was the principal residence of the Romanovs. It was built and developed by tsars Alexey Mikhailovich and Feodor Alexeevich. The сhildhood of Peter the First was connected with the palace of his father and brother. Peter included Kolomenskoye into the festivities organized on the occasions of the conquest of Azov and victory in Poltava battle, built two bogus earth forts and a funny palace, and accommodated his regiments there in 1712. Upon enunciation of Peter the Emperor, he ordered to restore the Kolomenskoye palace and invited architects F. Chekalovski, M. Zemtsov, and I. Ustinov for that purpose. Archeologists have explored the remnants of the 17th-century palace quite well but the results of their studies are not brought in the academic turnover yet. Archive, architectural and museum investigations of Kolomenskoye in the 17th and the 18th centuries have advanced. Accumulated archive, graphic, architectural, material objects sources, and archeological records require comprehensive analysis of Kolomenskoye as the residence of Peter I. It is a chance to concentrate on the problem of succession and continuity of traditions in the culture of the epoch, to investigate Peter’s role in preservation of this succession, for the merit of Kolomenskoye restoration belongs to him. The comprehensive investigation of the residence has revealed the uniqueness of the transitory period culture, thereby defining anew the place of the epoch in the cultural space of Moscow.The reported study was funded by RFBR according to the research project № 20–09–42021.
Keywords: early Modern time; Peter the First; Kolomenskoye; residence; the Sovereign’s court; palace; inventories; interiors; archeology of transitory period; glazed tiles; stoves